(untitled) (Boca Raton, 2001)
Food Toxicology provides a comprehensive look at contemporary food toxicology issues. Its nine chapters, all authored by leading American academic experts, concisely address critical chemical food safety and food toxicology issues that emerged in the latter half of the last decade. Specifically, the book discusses food allergens and their diagnoses, biotechnology, estrogenic factors, and antitoxicants. It also addresses more traditional topics such as pesticide residues, food additives, plant toxins, microbial toxins, and food analysis
Độc chất học thú y,Độc chất học trong thực phẩm,Độc chất học thú y
Keywords: Food,Thực phẩm; Toxicology,Chất độc